Talar Neck Fractures: An Overview - S P P S Rao; Mazin S Ibrahim; Gurdip Chahal; James Ramos (Journal of Novel Physiotherapy and Physical Rehabilitation - Peertechz Publications, 2014)
Talar injuries are infrequently encountered in practice as the majority require a high energy force such as road traffic accident or fall from height and they are often presented as complex injuries. Talar neck fracture accounts for half of these injuries. Because of the high rate of avascular necrosis (AVN) and posttraumatic arthritis associated with these injuries, it is difficult to predict the prognosis of AVN with the current classification systems. The anatomical position, difficulty of surgical approaches and its complex blood supply add to the challenges. Early recognition and a robust management plan are essential in treating such injuries. Failure to recognize a displaced talus fracture can result in Osteonecrosis, osteoarthritis, malunion or non-union which affects the hind foot function and results in pain, loss of motion and deformity. The integrity of this bone is vital for the function of the ankle, subtalar and mid tarsal joints. This article is an overview of this challenging injury including the mechanism of injury, classification, management and rehabilitation.